(3EOGQI GdehGQO GdHTQjI (B:s (3YQV hJMdjd (B/s - (3UGdM, eMeO UGdMs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2004)
(3fTCI GOGQI GdehGQO GdHTQjI hJWhQgG, CgOGa GOGQI GdehGQO GdHTQjI hGdUaGJ GdQFjSjI deOjQgG, JMdjd hJhUja hJbjje GdhXGFa aj GdeDSSI hhVY Sde GdQhGJH hGdCLhQ dJdc GdhXGFa Ydi GNJdGa OQLGJgG hGdeQGcR ajgG, JNWjW Gdbhi GdYGedI, GdGNJHGQ hGdJYjjf, GdJOQjH, GdMhGaR, GdJWhjQ GdhXjaj Ch Gdegfj hGdeMGaXI Ydi GdcaGAGJ hJWhjQgG, Jbjje COGA GdYGedjf, GfgGA GdNOeGJ, YdGbGJ GdYGedjf, GOGQI GdCYeGd PGJ GdYdGbI HGdYGedjf hMbhbge, GdYGedhf hGUGHGJ GdYed, GdNOeGJ GdebOeI ddYGedjf, GSJYeGd GdMGShH(B.s
(3GdeQGLY U(B.219s
Keywords: (3EOGQI GdCaQGOs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs